Oxidative damage induced by combined exposure of titanium dioxide nanoparticles and cypermethrin in rats for 90 days. (January 2023) - Zhong, Mingqing; Zhang, Ruoyu; He, Xianzhi; Fu, Yu; Cao, Yuqing; Li, Yuanyuan; Zhai, Qingfeng
Titanium dioxide nanoparticles (TiO2 NPs) and cypermethrin (CPM) are widely used in various fields, and they can enter the environment in different ways. Combined exposure of TiO2 NPs and CPM may increase the accumulation of pollutants in organisms and affect human health. This study was undertaken to evaluate the oxidative and inflammatory parameters associated with the combined exposure of TiO2 NPs and CPM in rats. Twenty-four healthy male adult SD rats were randomly divided into four groups. The first group served as the control, while groups 2, 3, and 4 were treated with TiO2 NPs (450 mg/m 3 ); CPM (6.67 mg/m 3 ) or combined exposure of TiO2 NPs and CPM by inhalation for 90 days. We investigated the oxidative damage induced through combined exposure of TiO2 NPs and CPM in rats by evaluating hematology of the rats and determining the blood biochemical index. Our results demonstrated that inhalation of TiO2 NPs and CPM increased the levels of oxidative stress markers such as malondialdehyde and alkaline phosphatase in the serum of rats. These were accompanied by a decreased glutathione peroxidase and total superoxide dismutase levels. Furthermore, the level of glutathione peroxidase was further decreased while malondialdehyde was increased in the combined exposure of TiO2 NPs and CPM. Interestingly, pathological sections showed that different degrees of tissue injury could be seen in the liver and lung tissues of each exposure group. In summary, the combined exposure of TiO2 NPs and CPM can cause increased oxidative damage in rats and damage the tissue structure of the liver and lung.